Why case study research? Introduction to the field guide to case study research in tourism, hospitality, and leisure - Hyde, K.; Ryan, C.; Woodside, Arch (2012)
This chapter is a general introduction to the field of case study research in tourism, hospitality, and leisure. The chapter presents a brief review of the literature on the intra-individual logic of case study research. The chapter describes the "four horsemen" for doing case study research: accuracy, generality, complexity/coverage, and value/impact. Examples in the chapter that illustrate this perspective for undertaking case study research may impassion the reader to read through the field guide and personally engage in case study research - at least that is the hope of the editors of this field guide. Copyright © 2012 by Emerald Group Publishing Limited.